Implementation of The CTL Approach to Students' Learning Interest in Social Subjects in Primary Schools - Ramadhani, Aisyah; Fadhilla, Nurrizqi (Journal of Elementary School Education, 2024)
The purpose of this writing is to find out a description of the teacher's ability to apply the contextual and learning (CTL) approach, student interest in learning and student learning outcomes in social studies learning. This research uses a literature study method, namely by looking for sources from journals. Currently there is low interest students in social studies lessons and is a challenge for teachers in carrying out the teaching and learning process, this contextual and learning model approach is a learning method that can be applied by teachers to students in elementary schools. Social sciences subjects use the lecture method, which makes students bored and too monotonous. By applying contextual and learning approach with the aim of making students more active and increasing students' interest in learning, especially in social sciences subjects